Pengaruh Faktor Biaya, Faktor Pelayanan Dan Efektifitas Operasional Terhadap Performa Manajemen Logistik Perusahaan - Rina Ayu Vildayanti; Ravindra Safitra Hidayat; Muhamad Jusmansyah; Yugi Setyarko; Agus Sriyanto (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Successful companies will always practice logistics, supply chain and inventory management in order to reduce costs and provide services and operational effectiveness. Logistics in the current state of business coordinates and integrates all physical and non-physical movements and unites them with the organization, as well as information aspects. This study aims to analyze the impact of corporate logistics management which includes transportation, warehousing, packaging, inventory and information management to improve efficiency and effectiveness. Reducing the cost of each logistics activity will affect the total cost burden and improve company performance. This article will determine and define what logistics activities are key to the success of the company. Empirical research is based on articles that have been adapted and abstracted and become hypotheses that are generally understood after validation and proven by the results of the findings in these articles. Adequate inventory, storage, warehousing, transportation and information management are the main keys that logistics managers should practice to reduce the overall cost of the company. These findings include the affirmation of the need for logistics managers to optimally manage all logistics activities in order to achieve cost reduction, service improvement and operational effectiveness.